Epidemiology of occupational exposure to blood-borne viruses, postexposure prophylaxis and seroconversion over 10 years among healthcare workers - Lee, J.B.; Choi, J.S. (The Journal of hospital infection, 2023)
Healthcare workers (HCWs) are at increased risk of infection with blood-borne pathogens due to occupational blood exposures (OBEs). Early reporting, detection and postexposure prophylaxis (PEP) help to prevent infections. To investigate the incidence of OBEs, related epidemiological characteristics, PEP completion rate, time and reason for PEP discontinuation, and seroconversion rate reported over 10 years. This retrospective study analysed 1086 cases of OBE and PEP management from January 2012 to December 2021 among staff in a South Korean tertiary hospital. The mean incidence of OBE was 7.82 per 100 beds and 3.0 per 100 HCWs. Of 1086 cases of OBE, 633 (58.3%) HCWs required PEP and 453 (41.7%) did not. After OBE, 70.1% (444/633) of HCWs subject to PEP completed tracking, and 29.9% (189/633) stopped PEP tracking (P<0.001). The PEP completion rate showed a significant difference by gender (P=0.024), occupation (P<0.001) and exposure frequency (P<0.001). None of the 444 HCWs who completed PEP seroconverted to hepatitis B virus, hepatitis C virus, human immunodeficiency virus or Treponema pallidum (syphilis). The study findings demonstrate the need to improve follow-up care among HCWs following OBE. There is a need for education in healthcare facilities; moreover, establishing a national surveillance system is necessary to ensure that HCWs undergo PEP proactively and complete their follow-up visits.